Prevention of Stroke in Nonvalvular Atrial Fibrillation (Cardiovascular Journal, 2011)
Cerebro-vascular Disease (CVD) is the third most common cause of death in developed world after cancer and IHD. Atrial fibrillation (AF) is responsible in 45% of cases cardioembolism leading to CVD. Atrial fibrillation is considered to be one of the growing cardiovascular epidemics in the 21st century. Warfarin is a proven drug for prevention of stroke in patients with atrial fibrillation. Newer anticoagulants are being tried, fibrillation. Newer anticoagulants are being tried, but not yet well established by clinical trials. Separation of left atrial appendage from circulation by surgery or device implantation is a promising one in this field. Key words: Atrial fibrillation, Stroke, Left atrial appendage occlusion device DOI: http://dx.doi.org/10.3329/cardio.v1i1.8217 Cardiovasc. j. 2008; 1(1) : 64-71